THE EFFECT OF LIMING, LIQUID AND POLY ALUMINUM CHLORIDE TO IMPROVE WATER QUALITY - Rahma Liani; Budijono Budijono; Sampe Harahap (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTIn general,  peat water has various acidity level water. To improve the quality of that water, addition of lime and coagulant such  as alum and poly aluminium chloride is necessary.A research aims to find out a dose of lime, alum and PAC to improve water quality has been conducted in March-April 2019. Water samples were taken fromthe Wonosari Village, Bengkalis. This research used experimental method, data were analyzed according to the complete random design model. There  were 9 treatments applied namely9 different dose of lime, alum and PAC : P1 (500mg lime,170mg alumand630mg PAC), P2 (500mg lime, 340mg alum and560mg PAC) P3 (500mg lime, 510mg alum and 490mg PAC), P4 (500mg lime, 680mg alum and420mg PAC), P5 (500mg lime, 850 mgalum and350mg PAC, P6 (500mg lime 1020mg alum and280mg PAC), P7 (500mg lime, 1190mg alum dan 210mg PAC), P8 (500mg lime, 1360mg alum dan 140mg PAC), P9 (500mg lime, 1530mg alum dan 70mg PAC). A packet of the  mixture   was mixedwith1L peat water and was kept for 30 minute. The water quality was then checked.Results shown that the best mixed dosage was P8 and P9 because it increased the pH of the water. The pH of peat water was improved, from 4 to 9. Data obtained shown that the mixture of lime, alum and PAC was effective for improving the quality of peat water.Keywords :acid water, calsium carbonat, coagulant and pH